Generating a Full Cycle of Alternative Current Using a Triboelectric Nanogenerator for Energy Harvesting - Aso Ali Abdalmohammed Shateri; Fengling Zhuo; Nazifi Sani Shuaibu; Rui Wan; Liangquan Xu; Dinku Hazarika; Bikash Gyawali; Xiaozhi Wang (Micromachines)
The triboelectric nanogenerator (TENG) has emerged as a promising technology for efficiently converting ambient mechanical energy into electrical energy. Among various designs, the disk-based rotational TENG has demonstrated significant potential, as it can continuously harvest energy in a sliding mode via a grating mechanism. However, horizontal mechanical energy is more common than rotational energy in many practical applications. Herein, the present study introduces a novel device: the double horizontal linear-to-rotational triboelectric nanogenerator (DHLR-TENG). This innovative approach utilizes a gear system to convert horizontal linear mechanical energy into electrical energy. The experimental results revealed that the DHLR-TENG produces a full cycle of alternating current (AC) when integrated into an electrical circuit. It consistently delivers robust performance with an open-circuit voltage of 544 V, a short-circuit current of 61.16 µA, and a maximum power output of 33.27 mW. Additionally, the device durability, capable of withstanding over 1,000,000 cycles, makes it highly effective for powering small electronic devices, such as charging capacitors and illuminating commercial LEDs. The DHLR-TENG’s versatility and efficiency mark it as a major advancement in energy harvesting, with broad implications for powering portable electronic devices in a wide range of environments.